Factors Affecting Dividend Policy in Indonesian State-Owned Enterprises (SOEs) - Putu Ayu Anggya Agustina; Elisabeth Ria Viana Praningtyas; Rini Subekti; Luh Putri Mas Mirayani (Universitas Prasetiya Mulya, 2022)
This study examines factors affecting dividend policy with firm size, leverage, and profitability as control variables. Among the management policies aimed at improving the welfare of stakeholders, the result is in the form of dividends. Investors who receive dividends from companies that distribute dividends expect the company's share price to increase. The study population was all publicly listed SOEs listed on the IDX in 2022, with 20 companies in the observation year for 11 years from 2011 to 2021. The determination of the sample in this study used the non-probability sampling method with purposive sampling technique so that the total sample into 220 observed companies. This study uses multiple linear regression. The results showed that dividend premium, free cash flow, and audit delay had a significant positive effect on dividend policy, and firm size, leverage, and profitability were able to be control variables for this direct relationship.